2021
DOI: 10.1155/2021/9980981
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology Combined with Bioinformatics to Investigate the Mechanisms and Molecular Targets of Astragalus Radix-Panax notoginseng Herb Pair on Treating Diabetic Nephropathy

Abstract: Background. Astragalus Radix (AR)-Panax notoginseng (PN), a classical herb pair, has shown significant effects in treating diabetic nephropathy (DN). However, the intrinsic mechanism of AR-PN treating DN is still unclear. This study aims to illustrate the mechanism and molecular targets of AR-PN treating DN based on network pharmacology combined with bioinformatics. Materials and Methods. The Traditional Chinese Medicine Systems Pharmacology database was used to screen bioactive ingredients of AR-PN. Subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…In addition, MAPK1, AKT1, TP53, RELA and JUN were considered core potential therapeutic targets of AR for treating diabetic nephropathy. Molecular docking showed that these core targets had a good binding affinity to quercetin, kaempferol, isorhamnetin and formononetin (Zhao et al, 2021). Astragalosides have neuroprotective, anticancer and antidiabetic activities, which are related to the core targets of STAT3, JUN and TNF (Zhang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MAPK1, AKT1, TP53, RELA and JUN were considered core potential therapeutic targets of AR for treating diabetic nephropathy. Molecular docking showed that these core targets had a good binding affinity to quercetin, kaempferol, isorhamnetin and formononetin (Zhao et al, 2021). Astragalosides have neuroprotective, anticancer and antidiabetic activities, which are related to the core targets of STAT3, JUN and TNF (Zhang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, MAPK1, AKT1, TP53, RELA and JUN were considered core potential therapeutic targets of AR for treating diabetic nephropathy. Molecular docking showed that these core targets had a good binding affinity to quercetin, kaempferol, isorhamnetin and formononetin (Zhao et al, 2021).…”
Section: Ppi Network Analysismentioning
confidence: 99%
“…Previous studies have reported on the various bioactive chemicals in astragalus root ( Bratkov et al, 2016 ) and related pharmacological pathways involving molecular targets, including antioxidants, anti-inflammatory response, and antiapoptosis, and cell cycle regulation ( Zhao et al, 2021 ). Astragalus root is also effective in reducing fasting blood glucose and albuminuria levels, in reversing the glomerular hyperfiltration state, and in ameliorating the pathological changes of early diabetic nephropathy in animal models ( Zhang et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, a phenolic flavonol compound, can be extracted from multiple Chinese medicine herbs, including Mulberry leaves, Radix Bupleuri , licorice, Astragali Radix, and Panax notoginseng ( Shi W. et al, 2021 ; Zhao J. et al, 2021 ; Chen et al, 2022 ; Tu et al, 2022 ). Accumulating studies have shown that quercetin has diverse pharmacological effects, including antioxidant, anti-aging, anti-fungal, anti-tumor, anti-inflammatory, anti-depressant, and hepatoprotective activities ( Arabpour et al, 2021 ; Zou et al, 2021 ; Chen et al, 2022 ).…”
Section: Exosomes As Delivery Vehicles For Compounds Isolated From Tcmmentioning
confidence: 99%